THE DEVELOPMENT OF LEAFLET FOR LOCAL HISTORY TEACHING MATERIALS - Maryanti, Maryanti; Ofianto, Ofianto; Zafri, Zafri (Indonesian Journal of History Education, 2019)
This article is written based on the thesis entitled ?The Development of Leaflet Media for Local History Teaching  Media? Grade XI at Senior High School (SMA) 6 Padang. This research is a developmental research, carried out because the students are yet to utilize the textbook as well as the other reading materials containing the relevant learning materials, thus their learning experience is less meaningful. The purpose of this research is to reveal the eligibility and practicality of leaflet as a History teaching material. The research method  refers to the mechanisms introduced by Borg and Gall. The objects of this research are the students of Sekolah Menengah Atas Negeri 6 Padang grade XI Social Science 4 whose number is 27 students, with 2 lecturers as the expert in material validators and 2 History teachers in grade XI Senior High School No. 6 Padang.according to the feedback from the students and teachers, the leaflet is eligible and practical to be used in the teaching and learning process of Japanese Colonialization.